Mentoring While Black & FemaleThe Gendered Literacy Phenomenon of Black Women Mentors - Juanita Johnson-Bailey; Tennille Lasker-Scott; Yolanda Sealey-Ruiz (Adult Education Research Conference, 2015)
Black women’s social positions in American society allow them to experience life in ways that are different than other women. In this study, we are suggesting that the mentoring that Black women give and receive is a form of literacy that is distinct.
Keywords: Mentoring; Black Women; Gendered Literacy; Higher Education